Analisis Infrastruktur Teknologi Informasi Menggunakan Metode VRIO dan PEST di PT Pelita Buana Jaya. - Adam Satria Mahendra; Handika Anjas Himawan; Zhoni Zhonatan Prabowo; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The rapid advancement of information technology has encouraged medical supply distributors to enhance system integration and operational efficiency. PT Pelita Buana Jaya, operating in Central Java, requires a strategic assessment of its IT infrastructure to support procurement, storage, and distribution activities. This study aims to evaluate the internal and external factors influencing the company’s IT performance using the VRIO and PEST methods. The VRIO analysis examines the strategic value, rarity, imitability, and organizational capability of the company’s technological resources, while the PEST analysis explores the influence of governmental regulations, economic conditions, social expectations, and technological developments. The findings show that PT Pelita Buana Jaya’s current IT infrastructure supports basic operations but lacks full integration, resulting in several operational limitations. Therefore, the company needs to strengthen human resource competencies and develop more integrated digital systems to improve competitiveness and service quality.